The Quality of Medical Advice In Low-Income Countries - Das, Jishnu (The World Bank, 2008)
This paper provides an overview of recent work on quality measurement of medical care and its correlates in four low and middle-income countries-India, Indonesia, Tanzania, and Paraguay. The authors describe two methods-testing doctors and watching doctors-that are relatively easy to implement and yield important insights about the nature of medical care in these countries. The paper discusses the properties of these measures, their correlates, and how they may be used to evaluate policy changes. Finally, the authors outline an agenda for further research and measurement